Current Knowledge in Genetics, Molecular Diagnostic Tools, and Treatments for Mantle Cell Lymphomas - Sethi, Shenon; Epstein-Peterson, Zachary; Kumar, Anita; Ho, Caleb (Frontiers in Oncology, 2021)
Mantle Cell lymphoma (MCL) is a mature B-cell lymphoma with a well-known hallmark genetic alteration in most cases, t(11;14)(q13q32)/CCND1-IGH. However, our understanding of the genetic and epigenetic alterations in MCL has evolved over the years, and it is now known that translocations involving CCND2, or cryptic insertion of enhancer elements of IGK or IGL gene, can also lead to MCL. On a molecular level, MCL can be broadly classified into two subtypes, conventional MCL (cMCL) and non-nodal MCL (nnMCL), each with different postulated tumor cell origin, clinical presentation and behavior, mutational pattern as well as genomic complexity. This article reviews both the common and rare alterations in MCL on a gene mutational, chromosomal arm, and epigenetic level, in the context of their contribution to the lymphomagenesis and disease evolution in MCL. This article also summarizes the important prognostic factors, molecular diagnostic tools, and treatment options based on the most recent MCL literature.